2000
DOI: 10.1557/proc-612-d6.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Tin Thin Films Deposited by Alcvd as Barrier for Cu Metallization

Abstract: In advanced multi-level metallization schemes, the application of copper as interconnect metal requires the prevention of Cu diffusion into the active area and into interlevel dielectrics by total encapsulation of Cu with barrier films. Critical requirements for diffusion barriers are very small thicknesses, low resistivity, low deposition temperature and conformality on high aspect ratio trenches and vias. For this application, we have studied TiN films deposited by atomic layer chemical vapour deposition (AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…In recent years, TiN research has focused on its applications in semiconductor device technology, such as Al diffusion barriers, gate electrodes in fieldeffect transistors and advanced metallizations and interconnects in ultra-large scale integrated circuits and solar cells. [1][2][3][4][5][6][7] In particular, recent studies have shown that TiN is an excellent ohmic contact for the widely studied n-type gallium nitride ͑Si-doped ␣-GaN͒ semiconductor technology, [8][9][10][11] due to its low-work function ͑3.74 eV͒, which is close to the electron affinity of GaN ͑4.1 eV͒. 12 As there is a strong miniaturization trend in microelectronics, smaller device sizes and increased densities demand the development of reliable electronic devices at the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TiN research has focused on its applications in semiconductor device technology, such as Al diffusion barriers, gate electrodes in fieldeffect transistors and advanced metallizations and interconnects in ultra-large scale integrated circuits and solar cells. [1][2][3][4][5][6][7] In particular, recent studies have shown that TiN is an excellent ohmic contact for the widely studied n-type gallium nitride ͑Si-doped ␣-GaN͒ semiconductor technology, [8][9][10][11] due to its low-work function ͑3.74 eV͒, which is close to the electron affinity of GaN ͑4.1 eV͒. 12 As there is a strong miniaturization trend in microelectronics, smaller device sizes and increased densities demand the development of reliable electronic devices at the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have attracted special interest for applications in different areas of semiconductor device technology, such as Al diffusion barriers, gate electrodes in field-effect transistors, and advanced metallizations and interconnects in ultralarge scale integrated ͑ULSI͒ circuits. [1][2][3][4][5][6] As the size of the components of ULSI circuits becomes smaller, the study of the electronic properties of the consisting materials should be addressed in the nanometer scale. Of special interest is the study of nanocrystalline TiN x films, which is highly demanding and may differ from previous ones conducted for simple metals such as Ag ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…As we found before [7], in such samples k F ℓ ≃ 1, where k F is the Fermi vector, and ℓ ∼ 0.3 nm is the mean free path. This short mean free path can be related to the enhanced Cl content (up to 3%), characteristic of films grown by the above method [8]. Four-probe resistance measurements were carried out by the standard low frequency (0.4-2 Hz) ac lock-in current source technique with the ac current 0.01-1 nA.…”
mentioning
confidence: 99%